Case report: Metastatic ovarian mucinous carcinoma to the breast: diagnostic challenges and pitfalls - Laokulrath, Natthawadee; Lim, Siew Kuan; Lim, Hwee Yong; Gudi, Mihir; Tan, Puay Hoon (Frontiers in Oncology, 2024)
Metastases to the breast from extramammary sources are extremely rare, with the ovary, primarily high-grade serous carcinoma, being the most common origin. We report a case of breast metastases from advanced stage ovarian mucinous carcinoma in a 48-year-old female— a case hitherto unreported in the literature. The case is noteworthy for its atypical presentation marked by an areolar rash, clinically suggestive of Paget disease of the nipple. This unique clinical scenario, coupled with histopathological examination revealing in-situ-like carcinoma component, posed a diagnostic challenge in discerning the tumour origin. We emphasize the need for heightened awareness among pathologists to avoid misdiagnosing metastatic carcinomas as primary breast tumours, a potential pitfall with significant clinical implications.